Studi Kualitatif Tentang Dampak Positif dan Negatif dalam Penyusunan Laporan Keuangan pada UD Sumber Makmur - Masyhuri, Muhammad Ade (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to identify the positive and negative impacts of financial statement preparation at UD Sumber Makmur, a small furniture enterprise. The research employs a qualitative descriptive method with a case study design. Findings reveal that while formal financial statement preparation is not fully implemented, potential benefits include improved accuracy in financial monitoring, ease in strategic decision-making, and enhanced credibility with external stakeholders. Key challenges include limited time, costs, and accounting knowledge. The owner's awareness of the importance of financial reporting indicates potential for future development. The study recommends training and accounting assistance to address these challenges, alongside adopting Micro, Small, and Medium Entity Financial Accounting Standards (SAK EMKM) as a strategic step to enhance transparency and credibility.